2013
DOI: 10.1021/jf4026585
|View full text |Cite
|
Sign up to set email alerts
|

Biophenols and Antioxidant Properties of Australian Canola Meal

Abstract: During the extraction of canola oil, large quantities of meal are produced. Extracting biophenols from Australian canola meal (ACM) adds value to an otherwise low-value agro-industrial byproduct. This study examined the biophenol content and the antioxidant activity of ACM, the impact of extraction conditions, and varietal differences. Sinapine was the principal biophenol in ACM. In crude and hydrolyzed extracts, 31 compounds were identified: 2 dihexosides, 2 organic acids, 4 glucosinolates, 17 sinapic acid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 40 publications
0
35
1
Order By: Relevance
“…However, water extracts appeared to have higher recovery. The data gathered from UV-vis spectra, ABTS scavenging activity, and relative retention times were compared with reference standards and literature data to characterize the chemical composition of CMEs as described previously [2]. The online-ABTS HPLC analysis showed that, generally, most detected compounds demonstrate good ABTS radical scavenging activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, water extracts appeared to have higher recovery. The data gathered from UV-vis spectra, ABTS scavenging activity, and relative retention times were compared with reference standards and literature data to characterize the chemical composition of CMEs as described previously [2]. The online-ABTS HPLC analysis showed that, generally, most detected compounds demonstrate good ABTS radical scavenging activity.…”
Section: Discussionmentioning
confidence: 99%
“…The TPC of various extracts in decreasing order was as follows: AE > BE > ME > EE > WE > CE > HE ( Figure 1). Various extracts were chemically characterized by HPLC-DAD-MS/MS using commercially available reference standards and spectral data from previous literature [2]. Different extracts showed different phenolic profile [35] that reflects the relative polarity of various extracting solvents.…”
Section: Phenolic Composition Of Canola Meal Extractsmentioning
confidence: 99%
See 3 more Smart Citations